A corpus-based lexical study of the frequency, coverage and distribution of academic vocabulary in Islamic academic research articles - Mohamed Ismail , Ahamed Shah; Engku Ibrahim, Engku Haliza; Mayinuer, Abudukeremu (2011)
One of the main problems faced by both teachers and learners in English for Academic Purposes pertains to the question of which words are worth focusing during teaching and learning. This corpus-based lexical study aimed to explore the use of words in Coxhead’s (2000) ‘A New Academic Word List (AWL)’ in academic journal articles in the field of Islamic studies. Around 472,621 word corpus, called the Islamic Academic Research Articles (IARA) corpus, was created for this study. The corpus consisted of 66 research articles written in English that were published in more than 10 different Islamic academic journals. Authentic and academic research articles written on Islam, and from Islamic perspectives covering a wide range of topics, were selected. The study found that the most frequent 317 AWL words which occurred in the IARA corpus was only 56% of Coxhead’s AWL of 570. This finding points to the need for a special AWL for students. Findings suggest the need to produce field-specific academic word lists incorporating all frequent academic lexical items necessary for the expression of the rhetoric of the specific research area. Findings also revealed that some of the words which were found in the present study were not found in Coxhead’s Academic Word List. This may be due to the general nature of the AWL. This suggests that vocabulary needs of students in Islamic studies are characteristically different from those of students in other disciplines. Researchers and teachers therefore need to deal with these learners separately.